T-cell motility methods and protocols - Verma, Navin Kumar ca. 20./21. Jh (Methods in Molecular Biology, 2019)
This volume discusses the latest developments in cellular, molecular, biochemical, and imaging assays to study the biology and functions of T-cells. The chapters in this book cover topics such as LFA-1/ICAM-1 interactions in T-cell motility; using 3D-SIM to dissect signaling cross-talks in motile T-cells; GapmeR-mediated gene silencing in motile T-cells; activity of cellular kinases in migrating T-cells; and computational analysis of protein-protein interactions in motile T-cells. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Cutting-edge and comprehensive, T-Cell Motility: Methods and Protocols is an essential resource for graduate students, postdoctoral fellows, and principal investigators working in the fields of immunology, T-cell biology, biochemistry, molecular biology, and imaging